Degradation behaviors and mechanisms of MoS2 crystals relevant to bioabsorbable electronics. (August 2018) - Chen, Xiang; Shinde, Sachin; Dhakal, Krishna; Lee, Suk; Kim, Hyunmin; Lee, Zonghoon; Ahn, Jong-Hyun
Abstract Monolayer molybdenum disulfide (MoS2 ) exhibits unique semiconducting and bioresorption properties, giving this material enormous potential for electronic/biomedical applications, such as bioabsorbable electronics. In this regard, understanding the degradation performance of monolayer MoS2 in biofluids allows modulation of the properties and lifetime of related bioabsorbable devices and systems. Herein, the degradation behaviors and mechanisms of monolayer MoS2 crystals with different misorientation angles are explored. High-angle grain boundaries (HAGBs) biodegrade faster than low-angle grain boundaries (LAGBs), exhibiting degraded edges with wedge and zigzag shapes, respectively. Triangular pits that formed in the degraded grains have orientations opposite to those of the parent crystals, and these pits grow into larger pits laterally. These behaviors indicate that the degradation is induced and propagated based on intrinsic defects, such as grain boundaries and point defects, because of their high chemical reactivity due to lattice breakage and the formation of dangling bonds. High densities of dislocations and point defects lead to high chemical reactivity and faster degradation. The structural cause of MoS2 degradation is studied, and a feasible approach to study changes in the properties and lifetime of MoS2 by controlling the defect type and density is presented. The results can thus be used to promote the widespread use of two-dimensional materials in bioabsorption applications. Biomaterials: Understanding how materials fade away The mechanism by which two-dimensional electronic materials decompose in an environment similar to that inside the human body has been identified by researchers in South Korea. Biodegradable, or transient, electronic devices disappear when no longer needed. In biomedical applications, for example, a transient sensor in the body degrades or dissolves, eliminating the need for surgery to remove it. Jong-Hyun Ahn from Yonsei University in Seoul and co-workers investigated the degradation of crystals of the two-dimensional semiconductor molybdenum disulfide (MoS2 ), each having the triangular shape. They showed that the rate of decomposition is dependent on the angle of misalignment between the two crystals: crystals with a larger misalignment biodegrade faster than those more closely aligned. This behavior indicates that intrinsic defects in the atomic structure of the material are the cause of the degradation. We present the degradation behaviors and mechanisms of CVD-grown monolayer MoS2 crystals relevant to bioabsorbable electronics, triggered and extended based on the intrinsic defects such as grain boundaries and point defects for their high chemical reactivity caused by broken lattice and dangling bonds. Higher misorientation angle leads to higher degradation speed. This work paves the way for lifetime modulation and bioabsorbable device application by using 2D materials.